Phytochemical screening and antioxidant activity of Terminalia muelleri benth. leaf extract - Nouran M. Fahmy; Eman Al-Sayed; Abdel Nasser B. Singab (Ain Shams University, 2017)
In the present investigation, leaves of Terminalia muelleri were assayed for their phytochemical constituents, as well as its free radical scavenging activity. The antioxidant effect was measured using 2,2-diphenyl-1-picrylhydrazyl (DPPH•) radical scavenging assay, the phytochemical constituents were screened to assess their corresponding effect on antioxidant activity. The results showed that the ethanol soluble fraction of T. muelleri possesses a potent radical-scavenging activity using the DPPH• (2,2-diphenyl-1-picrylhydrazyl) radical-scavenging assay (IC50 value = 2.7 μg/mL, while the standard ascorbic acid has an IC50 value = 10.5 μg/mL).